Effects of Implementing Efficiency Techniques in the Plastics Industry in Germany and Western Australia – A Comparative Modelling Assessment - Schlϋter, A.; John, Michele; Böhm, S.; Calisir, N.; Hesselbach, J. (Berlin Institute of Technology, Berlin, Germany and Middle East Technical University, Ankara, Turkey, 2012)
Plastics manufacturing is an important industry in many countries. Energy consumption in particular can be very high. Energy efficiency is an increasing area of management interest given pricing pressures on manufacturing companies around the world. In some cases simulation can help to predict the results of implementing different technologies to improve energy efficiencies. This paper focuses on the results of a simulation model which deals with the substitution of electric power with natural gas and the cooling of moulds by absorption chillers in plastics production. The methodology reviewed can result in significant reductions in energy demand and is also valuable when energy requirements for heating purposes are relevant. Germany and Western Australia both represent different climatic regions, but the modelling assessment on production facilities in both countries highlights the benefits of taking a whole systems approach to energy saving and energy efficiency in plastic production.